2015
DOI: 10.1017/cjn.2015.12
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Decomposition of Motion in Essential and Parkinsonian Tremor

Abstract: Background: Treatment options for essential (ET) and Parkinson disease (PD) tremor are suboptimal, with significant side effects. Botulinum toxin type A (BoNT A) is successfully used in management of various focal movement disorders but is not widely used for tremor. Method: This study examines complexity of wrist tremor in terms of involvement of its three anatomical degrees of freedom (DOF) in two common situations of rest and posture. The study examines tremor in 11 ET and 17 PD participants by kinematic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 35 publications
4
16
0
Order By: Relevance
“…At present, literature on PD tremor injection with BoNT A has not shown similar success as with essential tremor. Supporting evidence from previous tremor analysis data suggest that PD tremor is multi-component, especially compared with eT 21 . However, most studies of focal hand tremor emphasize only the injection of flexor and extensor muscle groups.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…At present, literature on PD tremor injection with BoNT A has not shown similar success as with essential tremor. Supporting evidence from previous tremor analysis data suggest that PD tremor is multi-component, especially compared with eT 21 . However, most studies of focal hand tremor emphasize only the injection of flexor and extensor muscle groups.…”
Section: Discussionsupporting
confidence: 78%
“…Tremor is complex, especially in the upper extremity, and its manifestation can change depending on posture, task, and body part 21 . Parkinson disease tremor is often described as "pillrolling"; however, this tremor is not isolated to the fingers.…”
Section: Effectiveness Of Bont a In Parkinson's Disease Upper Limb Trmentioning
confidence: 99%
See 1 more Smart Citation
“…As clinical examination is commonly insufficient, kinematic analysis can measure and display accurate tremor amplitude readings aiding clinicians to correctly target muscles contributing to tremor in the arm, unique to each patient [28,29]. Rahimi and colleagues demonstrated that analyzing wrist tremor movements visually (clinical assessment by experienced injector) and objectively (using kinematics) produced a 36% and 53% agreement in muscle selection in ET and PD participants, respectively [30]. This demonstrated the low agreement between clinical and objective assessments and highlighted the inherent difference between these assessment techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the lack of adequate tremor assessment tools and poor injection guidelines have limited the use of BoNT-A for ET. [14][15][16] The use of well-established kinematic technology for tremor characterization is a reliable and feasible methodology and can be used to accurately pinpoint tremulous muscle groups for BoNT-A therapy. 13,15,17,18 Thus, kinematics provides an individualized multijoint movement pattern that can reduce the likelihood of dose-dependent weakness and thereby improve the functional efficacy of BoNT-A for ET.…”
Section: Introductionmentioning
confidence: 99%